Seed quality characteristics of Pinus halepensis – seed germination strategy and early seedling growth - T. K. Tsitsoni (Web Ecology, 2009)
Pinus halepensis is a Mediterranean tree species occupying areas of high tourist interest, where it forms aesthetic and recreational forests. However, intense human pressure, adverse climatic conditions and overgrazing degrade Aleppo pine forest ecosystems and render the natural regeneration of this species difficult. The ecological, landscape, recreational and soil conservation uses of P. halepensis along with its aesthetic value, make this species important for landscape planning and multi-purpose forestry. For these reasons, artificial regeneration may be required in order to render ecosystem restoration faster. Although P. halepensis is characterized by a high germination capacity and a constant temperature of 20 °C is considered optimal for germination, no research has dealt with the germination behaviour and early growth of seedlings under alternative temperature conditions similar to those dominating outdoors. Moreover, little research was conducted on seed quality characteristics of this species. Thus, in this study seed quality of P. halepensis was estimated by measuring purity, number of seeds per kg, weight of 1000 seeds, average seed weight, seed moisture content and percentage of empty seeds. Also, seed germination capacity, germination rate, percentage of infected and not germinated viable seeds, abnormal seedlings as well as the total seedling length were studied under laboratory (alternative temperature) and chamber (constant temperature) conditions with the same photoperiod. Results showed that the percentage of empty seeds and abnormal seedlings was extremely low and the total germination percentage was very high (87–90%) in both environments. Germination capacity, germination rate and the total length of seedlings did not show any differences among the two growth environments.